Gambaran Mobilisasi Aktif Pada Pasien Post Sectio Caesar di Ruang Perawatan dan Observasi RSUD Wamena Jayawijaya Tahun 2024 - Hutagalung, Sondang Riyanti; Tridiyawati, Feva (Jurnal Ners, 2025)
Post-Caesarean section patients generally experience limited mobility due to pain and fear of the condition of the post-operative wound. However, it is very important to carry out active mobilization as early as possible because it can help reduce pain, speed up the healing process, and prevent complications that may arise due to immobilization. Thus, education and support for patients to mobilize in stages needs to be considered in order to improve post-operative recovery. This research is descriptive qualitative and the Normality Test used, namely Shapiro-Wilk, was taken from medical record data of mothers who gave birth by caesarean section. The research results show that the majority of respondents are aged 26-30 years, with the 2nd parity being the largest group. Most patients began active mobilization on the 2nd postoperative day (60%), and 90% of them were successful. All respondents (100%) felt the effectiveness and positive impact of active mobilization, which helped reduce pain, speed up recovery, and prevent complications due to immobilization.